I'm beginning to see the light [videorecording (DVD)] - Bacci, Mark; Khudyakov, Konstantin; Huston, Jack, 1982-; Cornish, Abbie, 1982-; Jackson, Brandon T., 1984- (Gravitas Ventures, 2025)
After losing his family in a brutal accident, ex-trumpeter Ezra finds solace as a lighthouse keeper. But when two visitors reveal their true motives, Ezra must decide: let the light back into his life or stay in the shadows.